Genomic constellations of RVA detected in Brazil from 1986 to 2016: a temporal and geographical distribution and occurrence of reassortments - Barros, Gerlane dos Santos; Barreto, Débora Machado; Jesus, Myrela Conceição Santos de; Batista, Marcus Vinicius de Aragão (ABCS Health Sciences, 2023)
Introduction: Species A rotavirus (RVA) infections are a major cause of severe gastroenteritis in children of <5 years worldwide. In Brazil, before vaccination, RVA was associated with 3.5 million episodes of acute diarrheal disease per year. Due to the segmented nature of their genomes, rotaviruses can exchange genes during co-infections, and generate new virus strains and new reinfections. Objective: To evaluate the genomic diversity of RVA isolated in Brazil in 30 years, between 1986 to 2016, to investigate possible changes in the frequency of genotype constellations before and after the implementation of the vaccine. Methods: In total, 4,474 nucleotide sequences were obtained from the Virus Variation Database. Genomic constellation was compared, and the proportion of rotavirus genotypes was analyzed by time and geographic region. Results: Our results showed that major known genotypes were circulating in the country during the period under analysis, with a prevalence of the G1P[8] Wa-like genotype, decreasing only in the period immediately after the introduction of the vaccine. Regarding the geographical distribution, most of our constellations, 62 (39.2%), and 50 (31.6%) were concentrated in the North and Northeast regions. Our analysis also showed the circulation of multiple strains during the periods when the DS-1-like and AU-1-like genotypes were co-circulating with the Wa-like genotype. Conclusion: Therefore, it is likely that inter-genogroup reassortments are still occurring in Brazil and so it is important to establish an efficient surveillance system to follow the emergence of novel reassorted strains that might not be targeted by the vaccine.